2020
DOI: 10.1111/ijfs.14866
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of SIMCA and PLS algorithms to detect adulterants in canola oil by FT‐IR

Abstract: Detection of adulterants in canola oil by FT‐IR and chemometrics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…GA, MD, and SPI had weak absorption peaks at 2930 cm −1 , characteristic of C–H bonds [ 34 ]. SPI, SS, and FS had strong characteristic peaks associated with C=O bonds around 1730 cm −1 [ 18 ], and all samples had strong peaks at 1000 cm −1 , characteristic of C–C bonds [ 35 ]. The absence of any new absorption peak in the microcapsule spectra indicated that the chemical structures of PPO and the encapsulating agents remained unchanged during microcapsule preparation.…”
Section: Resultsmentioning
confidence: 99%
“…GA, MD, and SPI had weak absorption peaks at 2930 cm −1 , characteristic of C–H bonds [ 34 ]. SPI, SS, and FS had strong characteristic peaks associated with C=O bonds around 1730 cm −1 [ 18 ], and all samples had strong peaks at 1000 cm −1 , characteristic of C–C bonds [ 35 ]. The absence of any new absorption peak in the microcapsule spectra indicated that the chemical structures of PPO and the encapsulating agents remained unchanged during microcapsule preparation.…”
Section: Resultsmentioning
confidence: 99%